2020
DOI: 10.1038/s41598-020-79129-w
|View full text |Cite
|
Sign up to set email alerts
|

Grip-force modulation in human-to-human object handovers: effects of sensory and kinematic manipulations

Abstract: From a motor control perspective, human-to-human object handovers can be described as coordinated joint-actions transferring the power over an object from a passer to a receiver. Although, human-to-human handovers are very reliable in terms of success, it is unclear how both actors plan and execute their actions independently while taking into account the partners behaviour. Here, we measured grip-forces of passer and receiver while handing over an object. In order to study mutual interaction in human-to-human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…After removing duplicates ( n = 3,639 removed) and after title and abstract screening ( n = 5,435 removed), the full text of 18 studies were scanned and 10 studies were found to meet our eligibility criteria [ n = 8 removed: no active handover = 4 ( Salleh et al, 2011 ; Parastegari et al, 2018 ; Kato et al, 2019 ; Neranon, 2020 ), non-relevant outcome = 2 ( Korkiakangas et al, 2014 ; Carfì et al, 2019 ), no human kinematic or force data = 2 ( Xie and Zhao, 2015 ; Chan et al, 2020 )]. Thus, we included 10 studies in our systematic review that investigated the characteristics of human-human handover actions and their influencing factors, such as the handover object weight and availability of sensory information ( Mason and Mackenzie, 2005 ; Becchio et al, 2008 ; Gonzalez et al, 2011 ; Meyer et al, 2013 ; Hansen et al, 2017 ; Controzzi et al, 2018 ; Bekemeier et al, 2019 ; Cini et al, 2019 ; Döhring et al, 2020 ; Sutiphotinun et al, 2020 ). See Figure 1 for a comprehensive flowchart of our search process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removing duplicates ( n = 3,639 removed) and after title and abstract screening ( n = 5,435 removed), the full text of 18 studies were scanned and 10 studies were found to meet our eligibility criteria [ n = 8 removed: no active handover = 4 ( Salleh et al, 2011 ; Parastegari et al, 2018 ; Kato et al, 2019 ; Neranon, 2020 ), non-relevant outcome = 2 ( Korkiakangas et al, 2014 ; Carfì et al, 2019 ), no human kinematic or force data = 2 ( Xie and Zhao, 2015 ; Chan et al, 2020 )]. Thus, we included 10 studies in our systematic review that investigated the characteristics of human-human handover actions and their influencing factors, such as the handover object weight and availability of sensory information ( Mason and Mackenzie, 2005 ; Becchio et al, 2008 ; Gonzalez et al, 2011 ; Meyer et al, 2013 ; Hansen et al, 2017 ; Controzzi et al, 2018 ; Bekemeier et al, 2019 ; Cini et al, 2019 ; Döhring et al, 2020 ; Sutiphotinun et al, 2020 ). See Figure 1 for a comprehensive flowchart of our search process.…”
Section: Resultsmentioning
confidence: 99%
“…In the other two studies, the roles were permanently assigned ( Cini et al, 2019 ; Sutiphotinun et al, 2020 ). In the remaining five studies, the experimenter took the role of the receiver and the subjects were only assigned the role of the giver ( Becchio et al, 2008 ; Gonzalez et al, 2011 ; Meyer et al, 2013 ; Controzzi et al, 2018 ; Döhring et al, 2020 ). All included studies were conducted using a within-subjects design ( Mason and Mackenzie, 2005 ; Becchio et al, 2008 ; Gonzalez et al, 2011 ; Meyer et al, 2013 ; Hansen et al, 2017 ; Controzzi et al, 2018 ; Bekemeier et al, 2019 ; Cini et al, 2019 ; Döhring et al, 2020 ; Sutiphotinun et al, 2020 ), although Meyer et al (2013) also used a between-subjects design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The baton was vertically transferred in handovers and a relationship between grip forces and load forces was measured, which was used to develop a controller for robotic grip forces given load forces. In [13], the effect of reaching velocities and sensory manipulations was seen on grip forces in human human handovers. In one of the studied cases, the giver's vision was manipulated by closing the eyes during the handover.…”
Section: Background and Related Workmentioning
confidence: 99%